Sikap Konsumen terhadap Multiatribut Produk Domino Pizza dengan Metode Fishbein di Depok - Wiwik Widiyanti (Cakrawala - Jurnal Humaniora, 2019)
Today's food business competition is tight, so every businessman is required to have a strategy in the field of marketing. To support this, Domino Pizza needs to conduct research on consumer attitudes towards the Domino Pizza product multi-attribute. This research is included in the type of qualitative research with 100 respondents based on convenience sampling by distributing questionnaires in Depok. Payment of data uses the fishbein method with texture attributes, pizza skin layers, toppings, prices, and packaging. From the results of research obtained about the level of consumer interest in pizza products are topping, texture, the thickness of pizza skin, price and final packaging. Based on the level of trust in the Domino product, the pizza that is placed first is the price, while the Pizza Hut product is Topping. Meanwhile, the attitude analysis of the overall attributes of domino pizza products is 74.34 and in pizza products but at 80.17. Thus, all consumers prefer pizza products but from domino pizza products. Although pizza products are superior in texture attributes because topping attributes are still inferior to pizza products, topping attributes have the highest importance, so if all attributes are taken into account, consumers prefer to use hut pizza products.  Keywords: fishbein method, consumer attitude, multi attribute